Hybrid CaCO3-mucin crystals: Effective approach for loading and controlled release of cationic drugs - Balabushevich, Nadezhda G.; Kovalenko, Ekaterina A.; Le-Deygen, Irina M.; Filatova, Lyubov Y.; Volodkin, Dmitry; Vikulina, Anna S. (Materials & Design, 2019)
Vaterite CaCO3 crystals are actively used as a biocompatible and degradable matrix for encapsulation of fragile biomacromolecules. However, the incorporation of small cationic drugs into the crystals remains awkward due to a poor binding of these drugs to the crystal surface and scarce retention inside the crystal pores. Herein, we achieve efficient drug loading and control over drug release performance via utilisation of hybrid CaCO3 crystals impregnated with mucin. The co-loading of mucin and anticancer drug doxorubicin (DOX) into CaCO3 crystals enhanced drug content in the crystals by ca 12 times giving DOX concentration of 1.3 mg g−1 CaCO3. Retention of DOX inside hybrid crystals is governed by strong electrostatic attraction to mucin matrix and significant narrowing of the crystal pores in the presence of mucin. At physiologically relevant conditions, DOX release kinetics strongly depends on the recrystallization of the porous vaterite to non-porous calcite that is regulated by mucin concentration. We believe that this study will help to design novel effective drug delivery systems able to load high amounts of drugs at mild conditions for sustained and controlled release of the drugs. This is indispensable for mucosal delivery where mucin produced by epithelial tissues is a main component.
CRIS-Team Scopus Importer:2021-06-08
Keywords: Aprotinin; Co-synthesis; Doxorubicin; Mucosal delivery; Prolonged release; Vaterite